Pengaruh Faktor Organisasi dan Individu Terhadap Kinerja Perawat Melalui Employee Well-Being - Syitharini, Niken; Achmadi, Hendra (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aimed to analyze the effects of internal service quality, job satisfaction, job commitment, and supervisor support on job performance, with employee well-being as a mediating variable. Methodology/approach: This research used a quantitative method with a Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis technique. The sample used in this study consists of 148 nurses. Data were collected using an online questionnaire. Results: The results of the study show that internal service quality has a significant positive effect on job satisfaction, job commitment, and employee well-being. Job satisfaction, job commitment, supervisor support, and employee well-being significantly and positively affect job performance. Job satisfaction has an indirect positive effect on job performance through employee well-being. Job commitment and supervisor support have positive but insignificant indirect effects on job performance through employee well-being. The mediation analysis results show that employee well-being partially mediates the effect of job satisfaction on job performance. Conclusion: Improving internal service quality, job satisfaction, commitment, supervisor support, and employee well-being can enhance nurses' performance. Limitations: This study used online data collection without supervision, the sample was limited to a single hospital, and there were other external factors not captured in the model. Contribution: This study contributes to hospital management by improving nurses performance through enhancing internal service quality, job satisfaction, supervisor support, commitment, and employee well-being.